TES DIAGNOSTIK (CIRI,SASARAN,SIFAT,LANGKAH-LANGKAH PENGEMBANGAN DAN PEMANFAATAN HASIL TES DIAGNOSTIK) - Achmad Rasyid Ridha; Asmira Efendi; Anisa Nur Khotimah (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2026)
Diagnostic tests are essential assessment instruments used to identify students’ initial learning conditions, including misconceptions, learning difficulties, and readiness to engage with instructional materials. Unlike summative assessments that emphasize final outcomes, diagnostic tests focus on students’ cognitive processes, providing teachers with in-depth information to design appropriate instructional strategies. This article aims to comprehensively examine the concept of diagnostic testing, including its characteristics, target users, nature, development procedures, and the utilization of diagnostic test results to enhance learning effectiveness and support differentiated instruction. This study employs a library research method by reviewing various academic sources, including books and national and international journal articles related to diagnostic assessment and educational evaluation. The findings indicate that diagnostic tests are characterized by their implementation prior to instruction, their non-summative function, and their ability to identify conceptual errors and learning barriers. The development of diagnostic tests must follow systematic steps, such as defining objectives, constructing test blueprints, developing test items, conducting validity and reliability testing, and revising instruments based on trial results. Furthermore, the utilization of diagnostic test results enables teachers to plan remedial and enrichment programs as well as implement differentiated learning strategies tailored to students’ needs. Therefore, diagnostic tests serve as a fundamental tool in adaptive instructional planning and contribute significantly to the continuous improvement of educational quality.